176 ALDOSTERONE EXCESS IS ASSOCIATED WITH TRUE TREATMENT RESISTANCE AS INDICATED BY SUSTAINED AMBULATORY BLOOD PRESSURE LEVELS AND LESS WHITE-COAT EFFECT. Issue 1 (1st January 2007) - Pimenta, E.; Pratt-Ubunama, M. N.; Gaddam, K. K.; Nishizaka, M. K; Oparil, S.; Calhoun, D. A.
Abstract : Purpose: Ambulatory blood pressure (BP) better predicts cardiovascular outcomes than office BP. The purpose of this study was to compare the 24-hour ambulatory blood pressure monitoring (ABPM) profile and the degree of white-coat effect (WCE) in resistant hypertensive subjects with or without hyperaldosteronism. Methods: Two hundred fifty-two subjects with resistant hypertension were prospectively evaluated with an early-morning plasma aldosterone and plasma renin activity (PRA), 24-hour urinary aldosterone and sodium, and 24-hour ABPM. Daytime, nighttime, and 24-hour blood pressure as well as nocturnal BP decline were determined. Hyperaldosteronism (H-Aldo) was defined as suppressed PRA (< 1.0 ng/mL/h) and elevated 24-hour urinary aldosterone excretion (> 12 μg/24 h). Results: Overall, the mean office BP was 160.0 ± 25.2/89.4 ± 15.3 mm Hg on an average of 4.2 medications. There was no difference in mean office BP values between the 59 subjects with H-Aldo and the 193 subjects with normal aldosterone levels (N-Aldo). However, daytime systolic (150.6 ± 14.6 vs 140.7 ± 18.0 mm Hg, p = .0002), daytime diastolic (88.8 ± 8.7 vs 82.4 ± 13.7 mm Hg, p = .0009), nighttime systolic (147.0 ± 17.2 vs 133.9 ± 18.6 mm Hg, p < .0001), nighttime diastolic (83.6 ± 8.7 vs 75.5 ± 13.9 mm Hg, p < .0001), 24-hour systolic (149.1 ± 15.2 vs 138.2 ±17.6 mm Hg, p < .0001), and 24-hour diastolic (86.7 ± 8.9 vs 79.8 ± 13.3 mm Hg, p = .0002) BP were all higher in H-Aldo than N-Aldo subjects. A WCE was present in 36.8% of the N-Aldo subjects but only 6.8% of H-Aldo. Systolic and diastolic nocturnal decline tended to be lower in patients with H-Aldo compared with N-Aldo. Conclusions: In spite of similar office BP, daytime, nighttime, and 24-hour ABPM levels were higher and there was less WCE in resistant hypertensive subjects with H-Aldo. These results suggest that high aldosterone levels impart increased cardiovascular risk not reflected by office BP measurements.